Network Analysis of Anxiety, Insomnia, Depression, and Suicide Attempts in Chinese Outpatients with Somatic Symptom Disorder - Fang J; Tang H; Liao H; Zhong Y; Li Y; Liao Y; Li Y (Neuropsychiatric Disease and Treatment, 2025)
Junning Fang,1 Hong Tang,1 Huiyun Liao,1 Yunhui Zhong,2 Yibo Li,3 Yuanping Liao,2 Yihui Li1 1Department of Psychology, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 2The Third People’s Hospital of Ganzhou, Ganzhou, Jiangxi, People’s Republic of China; 3Department of Psychiatry and Psychology, College of Basic Medical Sciences, Tianjin Medical University, Tianjin, People’s Republic of ChinaCorrespondence: Yihui Li, Gannan Medical University, Room 1-801, Teacher Building, No. 14, Ganzhou, Jiangxi, 341000, People’s Republic of China, Tel +8615879794780, Fax +0797 8169748, Email feizifen@gmu.edu.cnBackground: In clinical settings, somatic symptom disorder (SSD) has a significant impact on the psychological well-being of patients and is closely related to anxiety, sleeplessness, depression, and suicide. To provide novel insights into the management and rehabilitation of patients with SSD and the early detection of suicidal behavior, this study aimed to examine the relationship among anxiety, insomnia, and depression as well as that between these symptoms and suicide attempts in patients with SSD.Methods: A total of 899 individuals from Ganzhou People’s Hospital, Gannan Medical University’s First Affiliated Hospital, and Ganzhou Third People’s Hospital were enrolled. The GAD-7, ISI-7, and PHQ-9 were used to evaluate the severity of anxiety, insomnia, and depression, respectively. The EBICglasso function was used to construct a network graph of the symptoms of anxiety, insomnia, and depression, and we investigated the relationship between the mental health status of the patients and whether they had attempted suicide in the past.Results: The strongest centrality was found for “Waking up early”, followed by “Irritability”, “Suicide ideation”, “Nervousness”, and “Uncontrollable worry.” The five bridge symptoms included “Irritability”, “Waking up early”, “Suicide ideation”, “Concentration”, and “Guilt.” In addition, a suicide attempt was directly positively correlated with “Suicide ideation”, “Sleep dissatisfaction”, and “Sleep maintenance.” this indicated that the worse the sleep quality, the more likely it was to be associated with suicidal behavior. There was no significant difference in network analysis between male and female patients.Conclusion: Based on this result, we can provide psychological treatment for patients with depression and anxiety symptoms. For insomnia symptoms, appropriate clinical medicine interventions can be supplemented while adjusting sleep habits. Treatment strategies targeting specific mental symptoms are required to alleviate or prevent common and regularly recurring mental syndromes, decrease the frequency of suicide attempts, and improve treatment outcomes in patients with SSD in China.Keywords: anxiety, insomnia, depression, suicide attempts, network analysis